Sustainability And Contribution Of Small Beading Industry In Improving The Welfare Of Village Community - Aslichah Aslichah; Lavenia Indanus Pratiwi; Khoiruddin; M. Fathurohman (Enrichment : Journal of Management, 2022)
The purpose of this study is to determine the efforts of craftsmen and the community in maintaining the sustainability of the small bead industry in improving the welfare of the community. This type of research is a qualitative research with a case study approach. The research was conducted at the center of the beading industry. The data collection technique is based on observation and interviews and documentation. The data analysis technique uses qualitative data analysis with the steps of the Miles and Huberman model. Test validity with Triangulation. The results of this study are 1. Efforts made by craftsmen in maintaining the sustainability of the beading industry, namely by maintaining aspects: marketing, maintaining quality and quality, consumer trust, regeneration of bead craftsmen, surrender and trust in the one who makes God Almighty. . 2. Contributions for craftsmen (entrepreneurs and workers) of Gudo beads are in the form of increasing welfare, namely sufficient income, so that craftsmen are able to meet their daily needs (clothing, food and boards) and send their children to higher education, facilitated health. .